Mental health knowledge and common misconceptions in a master of chiropractic final year cohort. Issue 3 (8th May 2017) - Ferrari, Madeleine; Whillier, Stephney
Abstract : Purpose: Given rising incidence rates of mental health concerns in the general population it is important for all primary health care practitioners, including chiropractors, to have knowledge of such presentations. Practitioners frequently need to refer clients to appropriate mental health services, manage the biopsychosocial aspects of all conditions they treat, and work in interdisciplinary teams to ensure optimal patient outcomes. The mental health literacy (MHL) of these practitioners may, however, be influenced by both learnt knowledge and common misconceptions. The purpose of this paper is to investigate the MHL of a final year Master of Chiropractic student cohort. Design/methodology/approach: In total, 89 students completed an online questionnaire assessing mental health knowledge, misconceptions, perceived value of such knowledge for practicing chiropractors and demographic information. Findings: Student knowledge of the primary symptoms for depression and schizophrenia was competent, similar to community samples. However a high false positive response suggested students were poor at mental health differential diagnosis. A high number of common misconceptions about mental health were also endorsed, particularly in relation to depression, anxiety and suicide. Age and value of such knowledge seemed to predict greater MHL. Research limitations/implications: The present study offers direction for chiropractic education. In addition to content-based education, MHL may improve through targeting the students' perceived value of the information for chiropractors and combating common misconceptions. Future research could evaluate the incremental value of these approaches, and assess subsequent behavioural responses such as the students' confidence in managing patients with mental health concerns, and knowing when to refer on. Originality/value: Taken together, the current results suggest chiropractic students are able to identify symptoms causing distress; however tend to over-pathologise and endorse false symptoms as indicative of specific mental illnesses. In other words, students are poor at mental health differential diagnosis. Students also seemed to simultaneously hold a large number of misconceptions about mental health in general. It is of great importance to better understand gaps in student knowledge about mental health to prepare them for working with patients in a health setting.